Pendampingan Pelatihan Pengembangan Sistem Akademik di Sekolah Dasar - Enjang Yusup ali (Universitas Pendidikan Indonesia, 2023)
Assistance in training for academic system development in elementary schools is a program that aims to help improve the quality of the academic system in elementary schools. Mentoring is provided by a facilitator who has knowledge and experience in the field of education, working together with school principals and teachers in developing a better academic system. At the initial stage of the program, a needs analysis is carried out to determine problems that arise related to the academic system. Next, a follow-up plan is made to overcome the problem. During the training, materials related to the development of academic systems and practicums are provided to improve abilities in developing these systems. After the training is over, an evaluation is carried out to evaluate the effectiveness of this mentoring program, including measuring the increase in ability to develop the academic system after the implementation of the new system itself. The presence of this system development training assistance program will have a positive impact on the quality of education at the elementary school level as a whole.